Asymptotic behavior of solutions of pulse systems with small parameter and markov switchings. II. Weak convergence of solutions - Sverdan, M. L.; Tsar’kov, E. F.; Yasinsky, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We consider pulse systems with Markov switchings. We study the problem of the uniform boundedness of solutions of such systems and the stability of the systems with respect to the limit equation.